(untitled) (Tempo e Argumento, 2022)
In Argentina, shooting practice was compulsory in national schools from 1905 onwards and in incorporated schools since 1907. Those who promoted its compulsory nature sought not only to guide youngsters in shooting practice, but to promote this practice beyond the school setting, urging them to join shooting clubs and, especially, spreading among them a set of specific values associated with shooting practice. However, although shooting practice among young students was compulsory and reached a group of youngsters, its supporters did not achieve the desired goals of expanding shooting practice to more people and beyond school time. First, this article presents the characteristics that shooting practice had in secondary education facilities and the various initiatives that its supporters advocated for its growth and expansion. Second, the goals pursued by players when promoting shooting practice are analyzed. Finally, stock is taken from the perspective of the scope and constraints that shooting practice had within the period among students.